Teacher's Needs Analysis for English Reading Modules in Junior High Islamic Schools Based on Integrated Curriculum Standard - Maryanti, Tri; Wahyuni, Sri; Widhiyanto (Language Circle: Journal of Language and Literature, 2025)
English is an essential language used in various aspects of life, and formal education remains the primary setting where students learn English. In Indonesian Junior High Schools, English is commonly taught using resources provided by the school, with textbooks or learning modules serving as key materials. Most of these schools have adopted the Emancipated Curriculum (Merdeka Curriculum) while some, particularly Islamic schools, supplement it with the Integrated Islamic School Network (JSIT) Curriculum. The JSIT Curriculum combines an integrated learning system with a full-day school model, emphasizing Islamic values and character building. Given these unique educational settings, it is important to explore teachers’ specific needs for English reading modules that align with the characteristics and goals of Islamic schools. This qualitative study involved 25 English teachers from Islamic junior high schools in Magelang Regency. Data were collected through questionnaires and interviews. The results reveal that teachers encounter challenges in teaching reading comprehension, primarily due to a lack of suitable learning resources reflecting Islamic schools' identity and educational objectives. Therefore, there is a significant need to develop English reading modules tailored to the values, vision, and mission of Islamic education to enhance classroom instruction.